Ethik in pädagogischen Beziehungen - Berndt, Constanze; Häcker, Thomas; Walm, Maik (Verlag Julius Klinkhardt, 2022)
The question of ethics in pedagogical relationships, i.e., what is to be evaluated as right or wrong, appropriate or inappropriate, required or to be omitted, arises again and again at any time. This is currently impressively demonstrated by the ambivalences of the regulation of closeness and distance as well as the intersubjective recognition process, which have become alarmingly visible in the wake of the numerous uncovered cases of forcibly imposed closeness and other forms of violence. The authors shed light on questions of ethics in pedagogical relationships from different disciplines and invite us to reflect and think further.